Визначення якісних показників роботи приводних систем бурового верстату - Хілов, Віктор Сергійович (НТУ "ХПІ", 2010)
Is lay down and solve problem on the definition of the quality factor of drive rotation and up-dawn operations drilling line. Is accomplished analysis the stability of the combined manipulation system. Is established that exponents the quality factors of manipulation in the research systems of manipulation from hysteresis control current with allocated and concentrated fuzzycorrection are preserved at the variations of the parameters of control object in band ±25%.
Definition of drilling rig drive systems the qualitative measures
Keywords: привод транзисторний; операція спусково-підйомна; ПІД-регулятор; фаззи-корекція